Forming limit prediction of sheet metals by M-K model with various yield functions. (2017) - Zhu, Jie; Huang, Shangyu; Liu, Wei; Hu, Jianhua; Zou, Xifan
In order to investigate the influence of yield function on the accuracy of predicting forming limit curve (FLC) for sheet metal, Mises, Hill48 and Yld2000-2d yield functions were implemented in the M-K model. The parameter identification methodology of Hill48 and Yld2000-2d anisotropic yield functions was also investigated. For the AA5182-O aluminium alloy and TRIP780 steel sheets, the parameters of yield functions were identified respectively and the FLCs were numerically predicted with the identified yield functions. By comparison of the predicted uniaxial yield stresses, uniaxial anisotropic coefficients and FLCs with the experimental results, the Yld2000-2d yield function is found to be more accurate for modelling the anisotropy and formability of sheet metal than Mises and Hill48 yield functions, especially in the biaxial tension region of FLC.